The turn of the page: spoken quotation in shared reading. Issue 4 (1st October 2020) - Gordon, John
ABSTRACT: This article examines spoken quotation in literary study during discussion of novels in junior and senior classrooms. It focusses on teachers' third-turn exposition for literary-critical talk, a space where the modality of texts is transformed from print to oral expression. Teachers' spoken quotation develops students' sensitivity to how literary texts position their readerly perspective and response. Purposed to disciplinary pedagogic goals, spoken quotation itself has positioning influence, as teachers of literature guide students through multiple orientations to text even within single conversational turns. Methodological innovation adapts conversation analysis to account for the introduction of study texts to talk, the turn of the page as embedded quotation. Called QuoTE analysis, it draws on Bakhtin's dialogic concept of heteroglossia to demonstrate how spoken quotation in exposition performs, foregrounds and invites changing reader-orientations. Analysis of transcript data additionally finds that teachers' exposition positions students' readings explicitly and tacitly, using the modal resources of spoken quotation with methodic subtlety.